The Coombs A House of Memories - V. Lal, Brij (ANU Press, 2014)
The Coombs Building at The Australian National University is a Canberra icon. Named after one of Australia's greatest administrators and public intellectuals-'Nugget' Herbert Cole Coombs-for more than forty years the building has housed two of the University's four foundational Schools: the Research School of Pacific and Asian Studies and the Research School of Social Sciences. This volume of recollections is about the former. It looks at life in the building through the prism of personal experience and happenstance. Part memoir, part biography, and part celebration, this book is about the people of Coombs, past and present. Through evocative and lucid reflections, present and former denizens of the building share their passions and predilections, quietly savour their accomplishments and recall the failings and foibles of the past with a kindly tolerance.